Trajectories of Research in Translation Studies - Tymoczko, Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe article sums up the principle trajectories of research in translation studies that are likely to be productive in the coming decades. I focus on six broad areas. The first encompasses attempts to define translation: this includes research as diverse as examinations of particular linguistic facets of translation, corpus studies of translation, descriptive historical studies, and analysis of think-aloud protocols. The second area of research pertains to the internationalization of translation, which challenges basic Western assumptions about the nature of translation and generates new case studies that shake the foundations of translation theory and practice as they are known at present. Changes in translation theory and practice associated with emerging technologies and globalization constitute the third research area to be discussed. The fourth strand is the application to translation of various interpretive perspectives based on frames from other disciplines. The last two branches of research have to do with the relationship of translation studies to cognitive science and neurophysiology. The article closes with some general observations about the implications for translation research as a whole and the structure of translation studies entailed by the six areas discussed.